The relationship delay in referral with maternal mortality Dr. M. Djamil central general hospital Padang - Ibnu Razi Mulya Hasjmy; Ferdinal Ferry; Hafni Bachtiar (Universitas Andalas, 2022)
Introduction: Maternal mortality is maternal death during pregnancy, childbirth, and 42 days after delivery. Maternal Mortality Rate (MMR) is the number of maternal deaths per 100,000 live births. There was an increase in MMR in Indonesia on 2012 compared to 2007 which is 228 per 100,000 population. There were 17 maternal deaths at Dr. M. Djamil Hospital throughout 2019. Delay in referral can cause death for both mother and infantObjectives: This study aims to determine the relationship between delay in referral and maternal mortality in obstetric emergencies that came to the emergency unit at Dr. M. Djamil Hospital, Padang.Methods: This study used a cross-sectional comparative study design conducted on 90 pregnant women who visited Dr. M. Djamil Padang Hospital from January - February 2021. All data were then analyzed using univariate and bivariate analysis with appropriate statistical tests.Results: The mean age of the study subjects was 25.34 ± 5.99 years old with 12.21% of sample were nullipara, 21.27% primipara, 61.83% multipara, and 4.58% grande multipara. From the questionnaire, 54.3% were late to refer. From the medical records, it was found that in the group who died, 94.5% experienced a delay in referral and bivariate analysis showed a relationship between late referral and maternal mortality (p = 0.000).Conclusion: There is a significant relationship between late referral and maternal mortality at Dr. M. Djamil Central General Hospital PadangKeywords: Maternal Mortality Rate; late referrals; pregnant women